Oxidative Stress-Related DNA Damage in Patients with Idiopathic Granulomatous Mastitis: A Prospective Case-Control Study - Gonultas C.; AKÇAKAYA A.; KOÇYİĞİT A.; ŞİŞMAN G.; PAPİLA B.; VELİDEDEOĞLU M.; DAGMURA H. (My University, 2026)
Background/Objectives: Idiopathic granulomatous mastitis (IGM) is a rare, benign, chronic inflammatory disease of the breast that may present with recurrent and treatment-resistant courses and can clinically and radiologically mimic breast cancer. Despite its benign nature, IGM may significantly impair quality of life, and its underlying pathophysiology remains unclear. This study aimed to evaluate oxidative stress and DNA damage in patients with IGM. Methods: In this prospective case-control study, 28 patients with clinically and histopathologically confirmed idiopathic granulomatous mastitis who had not received corticosteroid or immunosuppressive therapy within the previous six months were enrolled. An age-matched control group of 27 healthy women was included. Venous blood and urine samples were collected for the assessment of total oxidant status (TOS), total antioxidant status (TAS), and calculation of the oxidative stress index (OSI). Mononuclear leukocyte DNA damage was evaluated using the alkaline Comet assay, and urinary 8-hydroxy-2 \"-deoxyguanosine (8-OHdG) levels were measured by ELISA. Sociodemographic data, laboratory and imaging results of the patients were also evaluated. Results: The mean ages of the patient and control groups were 37.3 +/- 5.3 and 35.4 +/- 8.6 years, respectively, with no significant difference (p = 0.081). Patients exhibited significantly higher inflammatory markers and oxidative stress parameters, including TOS, OSI, and urinary 8-OHdG (p < 0.05), whereas TAS did not differ between groups (p = 0.534). Comet assay analysis demonstrated significantly increased tail intensity (%) and tail moment in the patient group (p = 0.029 and p = 0.016). Conclusions: IGM is associated with increased oxidative stress and mononuclear leukocyte DNA damage. These findings suggest that oxidative stress-induced DNA damage may play a role in the pathophysiology of IGM and highlight the potential value of antioxidant-based therapeutic strategies as adjunctive treatment options.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Tıp Genel & Dahili; Klinik Tıp; Klinik Tıp (Med); Medicine General & Internal; Clinical Medicine; Clinical Medicine (Med); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine